The Ebola-Glycoprotein Modulates the Function of Natural Killer Cells - Edri, Avishay; Shemesh, Avishai; Iraqi, Muhammed; Matalon, Omri; Brusilovsky, Michael; Hadad, Uzi; Radinsky, Olga; Gershoni-Yahalom, Orly; Dye, John M.; Mandelboim, Ofer; Barda-Saad, Mira; Lobel, Leslie; et al. (Frontiers in Immunology, 2018)
The Ebola virus uses evasion mechanisms that directly interfere with host T-cell antiviral responses. By steric shielding of HLA-I, the Ebola glycoprotein (GP) blocks interaction with T-cell receptors (TCRs), thus rendering T cells unable to attack virus-infected cells. It is likely that this mechanism could promote increased natural killer (NK) cell activity against GP-expressing cells by preventing the engagement of NK inhibitory receptors; however, we found that primary human NK cells were less reactive to GP-expressing HEK293T cells. This was manifested as reduced cytokine secretion, a reduction in NK degranulation and decreased lysis of GP-expressing target cells. We also demonstrated reduced recognition of GP-expressing cells by recombinant NKG2D and NKp30 receptors. In accordance, we showed a reduced mAb-based staining of NKG2D and NKp30 ligands on GP-expressing target cells. Trypsin digestion of the membrane-associated GP led to a recovery of the recognition of membrane-associated NKG2D and NKp30 ligands. We further showed that membrane-associated GP did not shield recognition by KIR2DL receptors; in accordance, GP expression by target cells significantly perturbed signal transduction through activating, but not through inhibitory, receptors. Our results suggest a novel evasion mechanism employed by the Ebola virus to specifically avoid the NK cell immune response.